Power Factor Enhancement in Solution‐Processed Organic n‐Type Thermoelectrics Through Molecular Design. (14th March 2014) - Russ, Boris; Robb, Maxwell J.; Brunetti, Fulvio G.; Miller, P. Levi; Perry, Erin E.; Patel, Shrayesh N.; Ho, Victor; Chang, William B.; Urban, Jeffrey J.; Chabinyc, Michael L.; Hawker, Craig J.; Segalman, Rachel A.
<x xml:space="preserve">Abstract</x> A new class of high‐performance n‐type organic thermoelectric materials, self‐doping perylene diimide derivatives with modified side chains, is reported. These materials achieve the highest n‐type thermoelectric performance of solution‐processed organic materials reported to date, with power factors as high as 1.4 μW/mK2. These results demonstrate that molecular design is a promising strategy for enhancing organic thermoelectric performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>